Zintensyfikowane działania rodziców jako cecha współczesnego rodzicielstwa. Rozważania teoretyczne - Mazurowska , Anna (Studia Edukacyjne, 2023)
The article analyzes selected theoretical categories relating to parenting from a social perspective. The common denominator of these categories are the intensive actions of parents towards children, aimed at ensuring the best conditions for their development. The main axis of the narrative is the category of overparenting and helicopter parents. Moreover, the text provides hypotheses as to why parents choose this model of supporting their children.